Seputar (R,S)-Submodul Prima-? Gabungan - Dian Ariesta Yuwaningsih; Fayi Salsabila Sumaryati (Jurnal Matematika, Statistika dan Komputasi, 2023)
Given ? and ? be commutative ring with unity. The (?, ?)-bimodule structure has beengeneralized into the (?, ?)-module structure. Likewise, primeness in a module has also beengeneralized to the (?, ?)-module structure. However, the existing prime definition onlyfocuses on scalar multiplication operations in modules. The ?-prime submodule is one of thegeneralizations of the prime submodule, which involves additive operations and scalarmultiplication in the module. This article presents a generalization of the ?-prime submodulesinto the (?, ?)-module structure, hereinafter referred to as the jointly ?-prime (?, ?)-submodules. Furthermore, at the end of this article some properties of the jointly ?-prime(?, ?)-submodule are presented.